Net-Centric Approaches to Intelligence and National Security - Ladner, Roy; Petry, Frederick E. (Springer US : Imprint: Springer, 2005)
Net-Centric Approaches to Intelligence and National Security considers the web architectures and recent developments that make net-centric approaches for intelligence and national security possible. The development of net-centric approaches for intelligence, national & homeland security applications has become a major concern in many areas such as defense intelligence and national and international law enforcement agencies, especially since the terrorist attacks of 9/11. Net-Centric Approaches to Intelligence and National Security presents developments in information integration and recent advances in web services including the concept of the semantic web. Discovery analysis and management of web-available data pose a number of interesting challenges for research in web-based management systems. Intelligent agents and data mining are among the techniques employed. A number of specific systems that are net-centric based in various areas of military applications, intelligence and law enforcements are presented utlilizing one or more of such techniques Net-Centric Approaches to Intelligence and National Security is designed for a professional audience of researchers and practitioners in industry. This volume is also suitable for graduate-level students in computer science. .